Method for recycling concrete construction waste and / or demolition waste

Through the combination of microwave treatment and mechanical treatment, the concrete blocks are microcracked and recycled aggregate extracted, and carbonized in the presence of carbon dioxide, which solves the problem of poor quality of recycled concrete aggregate and fine powder in the prior art, and achieves high cleanliness and high-quality recycled aggregate and fine powder, which is suitable for the manufacturing of new concrete structures.

CN119604476APending Publication Date: 2025-03-11INST NAT POLYTECHNIQUE DE TOU LOUSE +4
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380059195.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-13
Filing Date
2023-06-13
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When recirculating concrete aggregate and fine powder, it is difficult to effectively separate natural aggregate and residual mortar, resulting in poor quality of the obtained recycled aggregate, high water absorption rate, weak mechanical characteristics, and small amount of fine powder, which limits its application in new concrete structures.

Method used

The concrete block is formed by combining microwave treatment and mechanical treatment, and then the aggregate and fine powder are recycled by mechanical extraction and carbonization in the presence of carbon dioxide to improve the quality and cleanliness of the aggregate and fine powder.

Benefits of technology

The recycled aggregate obtained by this method has higher cleanliness and quality, significantly improved water absorption and mechanical properties, increased fine powder amount, can be used in the manufacturing of new concrete structures in a larger proportion, and is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604476A_ABST
    Figure CN119604476A_ABST
Patent Text Reader

Abstract

The invention relates to a method for recycling concrete waste from construction and / or demolition, comprising at least one step of microwave treatment of concrete blocks, at least one step of mechanical treatment, and at least one step of carbonization of recycled concrete aggregate and / or recycled recycled concrete fines; the invention also relates to a recycling device for carrying out said recycling method and recycled concrete aggregate obtained by a microwave treatment step and a mechanical treatment step of concrete blocks.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a method for recycling concrete waste from construction and / or demolition, comprising at least one microwave treatment step of concrete blocks, at least one mechanical treatment step, and at least one carbonization step of recycled concrete aggregates and / or recycled concrete fines, a recycling device for implementing the recycling method and recycled concrete aggregates obtained by the microwave treatment step and the mechanical treatment step of concrete blocks.

[0002] Concrete is one of the most widely consumed manufactured materials in the world. It consists mainly of aggregates (coarse and fine gravel) mixed with cement, sand and water. In particular, France's annual consumption of aggregates is 350 million tons, or 6 tons per capita per year and 17 kg per capita per day. Forecasts show that the demand for aggregates will continue to grow, especially for the construction of new buildings. Natural aggregates (NA) are usually obtained by mining alluvial, continental or marine sand and gravel deposits. Natural aggregates (NA) are not a renewable resource and, although they are technically unlimited, they are becoming increasingly difficult to obtain for social and environmental reasons. In particular, it has proven increasingly difficult to open new quarries to meet the demand for natural aggregates (NA), as these quarries can cause nuisance to nearby residents (noise, dust, increased traffic, etc.).

[0003] At the same time, the amount of material generated by the demolition or removal of buildings and infrastructure is increasing and will continue to increase in the coming years. In fact, buildings built during the reconstruction period of the 1950s are gradually approaching the end of their life cycle, which means that the amount of concrete that needs to be recycled will become considerable.

[0004] Furthermore, the calcination of natural limestone mineral resources needed to make cement produces almost half of the CO2 emissions associated with the manufacture of concrete, one of the most CO2-emitting materials produced by humans.

[0005] Recycling concrete or masonry materials (e.g., construction waste and demolition waste) has been proposed as a way to avoid landfills, reduce reliance on natural sediments, and manufacture new concrete structures while conserving natural aggregate resources.

[0006] Construction concrete waste and demolition concrete waste are usually recycled by crushing concrete blocks to form recycled concrete aggregate (RCA). Screening can also be carried out to separate RCA from fines. However, the recycling methods currently available are not completely satisfactory. The separation of NA from residual mortar is far from being optimized. The RCA usually obtained consists of NA, which is mainly combined with a large amount of residual mortar in the base concrete. In particular, a large part of the residual mortar is present in the NA, which is either adhered to the NA or in the form of aggregates at least comparable in size to the natural aggregates, thereby hindering the production of clean NA. Due to the high proportion of adhered cement paste, this RCA is of average quality compared to NA: RCA has a higher water absorption and weaker mechanical properties (lower impact resistance and / or higher brittleness) compared to NA. Concrete made from RCA mixed under normal conditions loses its workability when transported in drums, which sometimes makes it unsuitable for use after reaching its destination. The current concrete standard NF EN 206 / CN specifies the maximum proportion of RCA to replace natural aggregates in the manufacture of new concrete, and this proportion varies according to the type of RCA, especially its composition, and the exposure class of the structure to be built. Due to the poor quality of these RCA, they are currently mainly used in low-value-added structures, especially in road earthworks as low-value-added backfill, road capping layer or quarry backfill. However, the recycling capacity in the road construction field is not unlimited and this form of downcycling does not satisfactorily meet the criteria of sustainable development.

[0007] In addition, comminution significantly breaks up the NA, resulting in a reduction in the particle size of the NA compared to the initial particle size distribution and enriching the fines with NA fragments. Therefore, the recycled fines obtained have components that make it more difficult to recover and / or recycle. Finally, since most of the cement paste adheres to or is combined with the RCA, the amount of fines produced is small relative to the amount of mortar found in the concrete. Current industrial plants generally do not recycle the finely comminuted flakes, which are considered waste products.

[0008] Solutions have been proposed to improve the properties of RCA, thus moving towards a standard that can increase the proportion of RCA in new concrete structures, especially those with high added value. Examples include polymer-based chemical treatments, the use of mineral reinforcing agents or carbonization (e.g. the use of bacteria leading to the formation of calcium carbide).

[0009] In particular, international application WO2020 / 217232 describes a wet concrete mixture comprising hydraulic cement, water and carbonized recycled concrete aggregate. The carbonized recycled concrete aggregate is obtained using a method comprising at least one crushing step, at least one particle size separation step and a carbonization step, wherein the carbonization can be carried out simultaneously with the crushing step or the particle size separation step, or after one of these steps. In an embodiment, a mortar containing sand and cement is crushed and carbonized to form a coarse recycled concrete aggregate of 5 mm to 20 mm, which is then exposed to an atmosphere rich in carbon dioxide (CO2) and with a relative humidity of 55% to 65% to form a carbonized recycled concrete aggregate. These carbonized recycled concrete aggregates are then mixed with sand, water and cement to form new concrete. The recycled concrete aggregate of WO2020 / 217232 has the components of mortar (a mixture of sand and cement). The RCA obtained after carbonization is unclean and has a poorer quality than NA.

[0010] In addition, some publications envision using concrete fines directly in cement raw materials as a raw material for making clinker. For example, Schoon et al. [Cement and Concrete Composites, 58, 2015, 70-80] describe the incorporation of recycled concrete fines (5% to 15%) into cement raw materials to replace traditional siliceous materials. Different technical configurations are used to separate mortar fragments from aggregates and to separate the resulting fines from recycled sand. However, Schoon et al. point out that it is difficult to collect large amounts of fines.

[0011] Therefore, there is still a need for recycling methods that enable to obtain recycled concrete aggregates that are as clean as possible (i.e. contain as little residual mortar as possible) and / or of better quality, so that they can be used in a greater proportion to form new concrete structures. There is also a need for recycling methods that enable to produce large quantities of high-quality recycled concrete fines. In particular, there is a need for recycling methods that enable to recycle all the recyclable parts of concrete, i.e. natural aggregates (NA) and the mortar surrounding them.

[0012] The object of the present invention is therefore to overcome the drawbacks of the prior art and in particular to provide a method for recycling concrete waste from construction and / or demolition making it possible to obtain recycled aggregates RCA of better quality, in particular with regard to water absorption and / or mechanical properties and / or higher cleanliness; and recycled fines of greater quantity and / or better quality, in particular with regard to pozzolanic activity and / or hydraulic activity, said method being simple, industrially applicable, using abundant raw materials and being environmentally friendly.

[0013] A first subject of the invention is a method for recycling concrete from construction and / or demolition objects, characterized in that it comprises at least the following steps:

[0014] i) subjecting centimeter-sized concrete blocks from construction and / or demolition to one or more microwave treatment steps to form microcracked concrete blocks,

[0015] ii) one or more mechanical treatment steps to enable the extraction of recycled aggregate (hereinafter referred to as RCA) from said micro-cracked concrete blocks, which includes bare natural aggregate (NA) and natural aggregate (NA) combined with adhering residual cementitious matrix (or residual mortar); and recycled fines,

[0016] Furthermore, it also includes:

[0017] iii) one or more steps of carbonizing the recycled aggregate in the presence of carbon dioxide to form carbonized recycled aggregate (hereinafter referred to as CRCA), and / or

[0018] iv) one or more steps of carbonizing the recycle fines in the presence of carbon dioxide to form carbonized recycle fines.

[0019] The method of the present invention is simple and easy to implement, and the results are:

[0020] - at the end of step i), step ii) and step iii), carbonized recycled aggregate (CRCA) which is cleaner and / or of better quality, in particular in terms of water absorption and / or mechanical properties; and / or

[0021] - at the end of step i), step ii) and step iv), the carbonized recycled fines contain a large amount of cement paste and / or are of better quality, in particular in terms of pozzolanic activity after the production of amorphous silica by the carbonization step, said amorphous silica being particularly reactive in cementitious media.

[0022] The process may involve carbonization of RCA [step iii)], carbonization of recycled fines [step iv)], or carbonization of RCA and recycled fines [step iii) and step iv)].

[0023] Furthermore, the method is industrially applicable, uses abundant raw materials (concrete waste from construction or demolition), and can reduce environmental impact by recycling unused construction concrete or demolition concrete, while ensuring the use or recovery of CO2. The method of the present invention is a complete concrete recycling method, since it recycles all the initial concrete, i.e. natural aggregate (NA) as well as fines.

[0024] The method is a method for recycling concrete from construction and / or demolition, in particular in the field of construction and public works. In other words, the concrete can be concrete waste generated by the construction of buildings and / or road structures, waste generated by concrete production, concrete generated by the demolition of buildings or road structures, or a mixture thereof.

[0025] definition

[0026] In the present invention, the term "cement" is used to refer to hydraulic cementitious materials, i.e. finely ground inorganic materials which, when mixed with water, form a paste which sets and hardens by hydration reactions and hydration processes and which, after hardening, retains its strength and stability even under water (according to the definition of standard EN 197-1).

[0027] In the present invention, the term "cement paste" (hereinafter referred to as "CP") is used to refer to a mixture of cement and water, which hardens due to a hydration reaction. The cement paste may optionally contain one or more than one additive. The amount of cement paste adhering to the RCA is a criterion for the cleanliness of the RCA.

[0028] In the present invention, the term "concrete" is used to refer to a mixture of cement, aggregates (sand and gravel) and water. This is the starting material containing all the components (aggregates and cement paste) that will be recycled.

[0029] In the present invention, the term "natural aggregate (NA)" is used to refer to natural sand and gravel particles produced by mining alluvial, continental or marine sand and gravel deposits.

[0030] In the present invention, the term "recycled concrete aggregate (RCA)" is used to refer to sand and gravel particles from concrete and reused to replace NA, make concrete or for any other application. In the present invention, the term "recycled concrete aggregate (RCA)" is also called "recycled aggregate".

[0031] In the present invention, the term "carbonized recycled concrete aggregate (CRCA)" is used to refer to concrete aggregate carbonized by a dedicated accelerated carbonization process. In the present invention, the term "carbonized concrete aggregate (CRCA)" is also called "carbonized recycled aggregate".

[0032] In the present invention, the term "residual mortar" is used to refer to the mixture of cement paste and NA whose size is smaller than the sieve size of the RCA in question. Most of the residual mortar is found adhering to the surface of the RCA in question. Therefore, the definition of residual mortar varies depending on the particle size of the RCA in question. If G M It is RCA grade G M -G m The upper limit of the sieve aperture is G mIt is RCA grade G M -G m The lower limit of the sieve aperture is , then the residual mortar associated with this particle size of RCA contains a size of <G m In the present invention, the term "residual mortar" is also referred to as "residual cementitious matrix".

[0033] In the present invention, the term "fines" is used to denote a mixture of cement paste and NA, the size of which is smaller than the minimum size G of the finest fraction of RCA produced by the concrete recycling process. m .

[0034] In the present invention, the term "accelerated carbonization" is used to refer to a carbonization method in which the CO2 concentration is 250 to 12,000 times higher than the CO2 concentration of the earth's atmosphere (415 ppm), which can result in carbonization kinetics that are completed in a few minutes compared to natural carbonation, which takes years. In residual mortar, only cement paste will be carbonized because the NA contained in the residual mortar will not be carbonized. In the present invention, the term "carbonization" used alone is synonymous with "accelerated carbonization". Therefore, the term "accelerated carbonization" or "carbonization" is the opposite of the term "natural carbonization".

[0035] In the RCA of the present invention, the terms "bare natural aggregate", "clean natural aggregate" and "clean RCA" are synonyms. The bare natural aggregate in the RCA of the present invention preferably contains less than 5 wt% CP, more preferably contains at most 4 wt% CP, and even more preferably contains at most 3 wt% CP, relative to the total weight of the bare natural aggregate.

[0036] In the RCA of the present invention, the terms "natural aggregate combined with the adhesion residual mortar", "unclean natural aggregate" and "unclean RCA" are synonyms. The natural aggregate associated with the adhesion residual mortar in the RCA of the present invention preferably contains 5 wt% to 30 wt% CP, more preferably contains 7 wt% to 25 wt% CP, and even more preferably contains 10 wt% to 20 wt% relative to the total weight of the natural aggregate combined with the adhesion residual mortar.

[0037] Step i)

[0038] The centimeter-sized concrete blocks from construction and / or demolition used in step i) comprise bare natural aggregates (i.e. natural aggregates not combined with or not containing an adhering residual cementitious matrix), such as gravel or sand (i.e. gravel or sand "bare" or not combined with or not containing an adhering residual cementitious matrix), and natural aggregates such as gravel or sand combined with an adhering residual cementitious matrix. In other words, the centimeter-sized concrete blocks from construction and / or demolition used in step i) comprise natural aggregates (NA), such as gravel and / or sand, and cement paste. Thus, within the centimeter-sized concrete blocks, NA is combined with cement paste to form the centimeter-sized blocks.

[0039] In the present invention, the adhesive residual cementitious matrix comprises, for example, cement, sand, water and optionally one or more additives. Gravel or a mixture of sand and gravel can be used instead of sand. As mentioned above, the particle size of the sand and / or gravel in the cementitious matrix is ​​smaller than the particle size of the natural aggregate NA combined with the cementitious matrix.

[0040] Step i) enables the formation of a primary network of cracks within the concrete block, especially around the natural aggregates (NA) (texture release of aggregates); followed by the formation of a secondary network of cracks in the cement paste CP of the bonding matrix (physical release of aggregates and intensive fracturing of the cement paste CP). This results in selective fracturing of the concrete, which can separate the natural aggregates (NA) from the bulk of the CP of the bonding matrix without significant damage to the natural aggregates (NA).

[0041] In other words, secondary fracturing creates a dense network of (secondary) microfractures that are permeated with cement paste in a gel matrix, whether or not the cement paste is attached to the surface of natural aggregates; it enables the cement paste in a cementitious matrix to be released in a fines fraction, which facilitates the subsequent extraction step ii) and the carbonization step iii) of the cement paste in a cementitious matrix bound to certain natural aggregates and attached to their surfaces, and / or the carbonization step iv) of the cement paste present in large quantities in the recycled fines.

[0042] Therefore, the formation of the primary and secondary crack networks described above facilitates the subsequent step ii) of selectively releasing natural aggregate (NA) contained in the concrete of construction and / or demolition objects, thereby promoting the separation of NA from fines without decomposing NA.

[0043] In other words, the greater the number of microcracks per unit volume in the cement paste of the bonding matrix, the cleaner the obtained recycled concrete aggregate (RCA) (i.e., high NA content, low content of residual bonding matrix or adhering residual mortar, or even no residual bonding matrix or adhering residual mortar), and the greater the content of CP in the fine powder, the more effective the method, especially the subsequent steps ii), iii) and iv).

[0044] Unlike crushers that randomly break concrete (such as Figure 1 As shown in FIG. 1 , microwave treatment selectively weakens the cement paste CP in the cementitious phase without significantly changing the structure of the natural aggregate NA. Thus, the integrity of the natural aggregate NA is preserved and, by the combination of steps i) and ii), at least 75% by weight of the CP of the centimeter-sized concrete blocks from construction and / or demolition can be found in the recycled fines.

[0045] The microwave treatment in step i) may be carried out at sufficient incident power to cause cracking of the concrete blocks.

[0046] Preferably, the microwave treatment in step i) is carried out at a power of 1 kW to 50 kW, preferably 5 kW to 40 kW and more preferably 5 kW to 10 kW.

[0047] These powers are particularly suitable for processing 1 t / h of concrete blocks.

[0048] Preferably, the microwave treatment in step i) is carried out for a time (exposure time) of about 30 seconds to about 10 minutes, more preferably about 1 minute to about 5 minutes.

[0049] In the present invention, the term "centimeter size" relates to concrete blocks from construction and / or demolition objects, preferably, "centimeter size" means that concrete blocks from construction and / or demolition objects have a size of at most about 10 cm, more preferably a size of at most about 7 cm, most preferably a size of at most about 5 cm.

[0050] Preferably, the dimensions of concrete blocks from construction and / or demolition are at least about 1 cm, more preferably at least about 2 cm, and most preferably at least about 3 cm.

[0051] Step i) may be carried out by passing the concrete blocks through a microwave tunnel.

[0052] The microwave treatment i) can be carried out at a frequency of about 915 MHz to about 2450 MHz, more preferably at a frequency of about 915 MHz or about 2450 MHz. These frequencies are average frequencies of 902 MHz to 928 MHz and 2400 MHz to 2500 MHz, respectively.

[0053] Microwave treatment i) can be performed continuously or in pulsed mode (eg, with symmetrical square wave pulses lasting at least 1 second).

[0054] Depending on the size of the concrete blocks to be treated, a travelling wave or a standing wave propagation mode can be used (concrete blocks to be treated smaller than 5 cm: standing wave; concrete blocks to be treated larger than 5 cm: travelling wave).

[0055] Microwave processing i) can be performed in a reflecting cavity using guided waves or antennas.

[0056] The microwave treatment i) leads to drying of the material, and the evaporated water can advantageously be recycled, in particular for reuse in subsequent steps ii) to iv).

[0057] At the end of step i), the concrete block is called "microcracked" because the cement paste contained in said concrete block is macroscopically microcracked. Thus, the concrete block obtained in step i) comprises microcracked cement paste.

[0058] Step ii)

[0059] In step ii), the micro-cracked concrete block produced by step i) is subjected to one or more mechanical treatment steps.

[0060] Through step i), mechanical stresses favoring shear forces during step ii) help propagate cracks, fragmenting micro-cracked concrete blocks while limiting the rupture of NA and releasing recycled aggregate RCA including bare natural aggregate and natural aggregate combined with adherent residual cementitious matrix and natural aggregate combined with recycled fines.

[0061] Step ii) can extract recycled aggregate RCA from the micro-cracked concrete blocks, the recycled aggregate RCA comprising bare natural aggregate and natural aggregate combined with an adherent residual cementitious matrix (or an adherent residual mortar); and recycled fines. At the end of step ii), the recycled aggregate is separated from the recycled fines, and at least 75% by weight of CP in the initial concrete to be recycled is found in the recycled fines.

[0062] At the end of step ii), a fraction F1 of recycled aggregate RCA is obtained, which comprises bare natural aggregate and natural aggregate combined with an adhering residual cementitious matrix (or adhering residual mortar); and a fraction F2 of recycled fines.

[0063] The recycled aggregate RCA preferably has a particle size of about 1 mm or greater.

[0064] The bare natural aggregate preferably has a particle size of about 1 mm or greater.

[0065] The natural aggregate combined with the adhesive residual cementitious matrix (or adhesive residual mortar) preferably has a particle size of about 1 mm or larger.

[0066] According to a preferred embodiment of the present invention, the bare natural aggregate (natural aggregate combined with an adhering residual cementitious matrix or an adhering residual mortar, respectively) is selected from gravel, sand and mixtures thereof having a particle size of about 1 mm or more.

[0067] Gravel is generally defined as having a particle size greater than about 4 mm.

[0068] Sand is generally defined as having a particle size of 4 mm or less.

[0069] In the present invention, the particle size of RCA, gravel and sand is determined by methods well known to the skilled person, in particular by sieving (for example according to standard NF EN 933-1) (laboratory method) or by screening (industrial method).

[0070] The adhesive residual cementitious matrix combined with natural aggregate NA (or adhesive residual mortar) comprises natural aggregate NA, preferably natural aggregate NA having a particle size of less than about 1 mm.

[0071] The recycled fines (fraction F2) typically comprise cement paste and natural aggregate NA, such as sand, preferably sand having a particle size of less than about 1 mm.

[0072] The particle size of the recirculated fines (fraction F2) is preferably less than 1 mm.

[0073] In fraction F2, sand and cement paste may be in the form of mortar, in separate forms, or in a mixture of the form of mortar and in separate forms.

[0074] Step ii-1)

[0075] Step ii) preferably comprises at least one step ii-1) of grinding the micro-cracked concrete blocks.

[0076] The step ii-1) of grinding the micro-cracked concrete block may be performed using at least one impact crusher (e.g. a jaw crusher, a gyratory crusher, a cone crusher or an impact crusher) or a non-impact crusher (e.g. a roller mill such as a single roll crusher or a double roll crusher, or a high pressure roll crusher, also known by the acronym HPRC of "High Pressure Roll Crusher").

[0077] Preferably, the step ii-1) of grinding the microcracked concrete blocks is a non-impact grinding step. In this embodiment, the step ii-1) of grinding the microcracked concrete blocks preferably uses at least one non-impact crusher.

[0078] The advantage of a non-impact crusher is that it applies a continuous compressive shearing action. It can therefore prevent excessive damage to the natural aggregate NA and / or maintain the integrity of its grading and mechanical properties.

[0079] The non-impact crusher is preferably a roller mill, such as a single roller crusher or a double roller crusher. The roller mill can have smooth or toothed rollers.

[0080] By appropriately adjusting its operating parameters, in particular the feed rate, the rotational speed of one or more rollers, the spacing between the rollers and / or the applied hydraulic pressure, the crushing roller mill can produce a specific maximum particle size corresponding to the particle size of the natural aggregate NA in the initial concrete to be recycled.

[0081] The spacing of the rollers is adapted to the maximum particle size of the original aggregate (ie the natural aggregate NA in the initial concrete to be recycled), in particular to minimize its breakage.

[0082] The method may comprise a plurality of grinding steps ii-1), in particular by carrying out:

[0083] - multiple grinding steps ii-1) after the microwave treatment step i), or

[0084] - Multiple consecutive microwave treatment steps i) and grinding steps ii-1).

[0085] When multiple grinding steps ii-1) are carried out after step i), a series of non-impact crushers, such as roller mills, can be used by appropriately adjusting the operating parameters of the successive crushers, in particular the feed rate, roller speed, roller spacing and / or applied hydraulic pressure.

[0086] The roller spacing can be continuously reduced to produce smaller and smaller RCA aggregate particle sizes and to obtain the cleanest possible RCA aggregate (i.e. high NA content, low residual adhesive mortar or low bonding matrix content), thereby optimizing the production of recirculated fines.

[0087] When multiple consecutive steps i) and ii-1) are implemented, a single non-impact crusher, such as a roller mill, can be used after each step i), by appropriately adjusting its operating parameters, in particular the feed rate, roller speed, roller spacing and / or applied hydraulic pressure, so that RCA with increasingly finer maximum particle sizes can be continuously produced.

[0088] The grinding step ii-1) is advantageously carried out in a dry process. A dry process is particularly suitable because the preceding microwave treatment step i) helps to dry the material.

[0089] By one or more grinding steps ii-1), recycled aggregate RCA (natural aggregate with or without adhering residual cementitious matrix) is obtained, which preferably has a particle size G of at most about 45 mm, or at most about 25 mm, or at most about 11.2 mm, or at most 8 mm, or at most 4 mm. M(corresponding to the maximum particle size of the natural aggregate NA of the base concrete to be recycled), depending on the intended application and / or the particle size of the natural aggregate NA found in the initial concrete to be recycled (i.e. G M ≤45 mm, or G M ≤25 mm, or G M ≤11.2 mm or G M ≤4 mm).

[0090] Preferably, the minimum particle size G of the recycled aggregate RCA (natural aggregate with or without adhering residual cementitious matrix) obtained after the grinding step is m At least about 1 mm (G m ≥1 mm).

[0091] Step ii-2)

[0092] Step ii) may further comprise at least one screening step ii-2) (also called sieving), in particular after step ii-1). This step ii-2) enables the RCA aggregates and fines to be classified by particle size.

[0093] The screening step ii-2) can be carried out in a dry process or a wet process, preferably in a wet process.

[0094] The screening step ii-2) can be carried out using any type of vibrating screen, gyratory screen or rotary screen or sieve, preferably a rotary screen or a rotary gyratory screen. A rotary screen is also called a rotary screen, a rotary screen, a drum screen or a drum screen.

[0095] The screening step ii-2) can separate the fraction F1 of recycled aggregate RCA from the fraction F2 of recycled fines; and optionally separate the recycled aggregate RCA according to its particle size within the fraction F1.

[0096] The method preferably comprises a plurality of screening steps ii-2).

[0097] The one or more sieves used in the one or more screening steps ii-2) comprise a mesh suitable for allowing such separation.

[0098] The screen (or series of screens) preferably has a mesh size suitable for the crusher (or series of crushers) used in step ii-1) or step ii-1).

[0099] According to a preferred embodiment of the present invention, step ii-2) comprises a first screening step ii-2a) which allows separation of particles having a particle size G1 such that G m ≤G1≤G M Recycled aggregate RCA, or fraction G 1’to G1 so that G m ≤G 1’ <G1≤G M Recycled aggregate RCA.

[0100] For example, the particle size G1 of the recycled aggregate RCA separated in the first screening step ii-2a) is at least about 4 mm.

[0101] For example, the particle size G1 of the recycled aggregate separated in the first screening step ii-2a) is at most about 45 mm, or at most about 25 mm, or at most about 11.2 mm, or at most about 8 mm, depending on the intended application and / or the particle size of the natural aggregate found in the initial concrete to be recycled.

[0102] For example, the first screening step ii-2a) may separate RCA having a given size fraction of: 4 mm to 8 mm, or 8 mm to 11.2 mm, or 11.2 mm to 25 mm, or 25 mm to 45 mm.

[0103] The limits for the particle size fractions are provided for reference only and any other limits may be used depending on the intended application and / or the particle size of NA found in the original concrete to be recycled.

[0104] In the first screening step ii-2a), the recycled aggregate RCA (fraction F 1a ) and recycled fine powder (particle size F 2a ) and optionally from the smaller recycled aggregate RCA (fraction F 1b , Particle size F 1c etc.) are separated.

[0105] The recycled aggregate RCA of particle size G1 comprises bare natural aggregate and natural aggregate combined with residual cementitious matrix (residual mortar), preferably adhered to said natural aggregate.

[0106] Step ii-2) may further comprise a second screening step ii-2b) making it possible to separate the recycled aggregate RCA, whose particle size is G2 such that G m ≤G2<G1, or particle size G 2' to G2 so that G m ≤G 2' <G2≤G 1< G1≤G M .

[0107] For example, the particle size G2 of the recycled aggregate RCA separated during the second screening step ii-2b) is at most about 4 mm.

[0108] For example, when the first screening step ii-2a) is capable of separating RCA with a particle size of 4 mm to 8 mm, the second screening step ii-2a) can separate RCA with a particle size of 1 mm to 4 mm; when the first screening step ii-2a) is capable of separating RCA with a particle size of 8 mm to 11.2 mm, the second screening step ii-2a) can separate RCA with a particle size of 4 mm to 8 mm; when the first screening step ii-2a) is capable of separating RCA with a particle size of 11.2 mm to 25 mm, the second screening step ii-2a) can separate RCA with a particle size of 8 mm to 11.2 mm; when the first screening step ii-2a) is capable of separating RCA with a particle size of 25 mm to 45 mm, the second screening step ii-2a) can separate RCA with a particle size of 11.2 mm to 25 mm.

[0109] Preferably, the recycled aggregate RCA separated in the second screening step ii-2b) has a particle size G2 of at least about 1 mm.

[0110] In the second screening step ii-2b), the recycled aggregate RCA (fraction F 1b ) and recycled fine powder (particle size F 2b ) and optionally separated from smaller size recycled aggregate (fraction F 1c etc.) separation.

[0111] The recycled aggregate RCA of particle size G2 comprises bare natural aggregate and natural aggregate combined with residual cementitious matrix (residual mortar), preferably adhered to said natural aggregate.

[0112] Therefore, step ii) may include one or more screening steps ii-2). In particular, one or more screening steps [step ii-2a), step ii-2b), step ii-2c), etc.] may be required in order to separate the recycled aggregate RCA from the recycled fines as much as possible. This may depend specifically on the particle size distribution of the initial natural aggregate NA used in the construction and / or demolition concrete.

[0113] The method of the present invention, in particular step ii), may comprise a plurality of grinding steps ii-1) and a plurality of screening steps ii-2).

[0114] In this embodiment, step ii) may include:

[0115] - multiple grinding steps ii-1) and subsequent multiple screening steps ii-2), or

[0116] - Multiple consecutive grinding steps ii-1) and screening steps ii-2).

[0117] Step ii) preferably comprises a plurality of consecutive grinding steps ii-1) and screening steps ii-2).

[0118] At the end of step ii), in particular at the end of step ii-1) and step ii-2), the separated or recovered recycled aggregate RCA has a structure as close as possible to the natural aggregate NA of the original demolition material and / or building concrete.

[0119] Therefore, the inventive method produced by steps i) and ii) can obtain RCA aggregate with high cleanliness and a large amount of fine powder, because most of the RCA has been freed from the residual mortar (and cement paste contained in the mortar) adhering to the NA.

[0120] When the method comprises a plurality of screening steps ii-2), after step ii), the method may further comprise the step of combining the samples from different screening steps (F 2a 、F 2b 、F 2c The step of bringing together fine powders of different particle sizes (such as powders, powders, etc.)

[0121] The reuse of large amounts of fines from concrete construction waste and demolition waste as mineral additives to reduce the demand for concrete cement and / or as a component of raw materials for cement production is a potential vehicle for reducing CO2 emissions and the demand for natural resources used to make concrete.

[0122] At the end of step ii), in particular at the end of step ii-1) and step ii-2), the recycled concrete aggregate RCA obtained with a given size fraction of 1 mm or more preferably comprises from 65% to 95% by weight of NA with said given size fraction, more preferably from 70% to 90% by weight of NA with said given size fraction, even more preferably from 75% to 85% by weight of NA with said given size fraction, relative to the total weight of RCA with said given size fraction. This is also called recovery rate.

[0123] Preferably, the RCA obtained with a given size fraction of 1 mm or greater comprises at most 10 wt% CP, preferably at most 8 wt% CP, even more preferably at most 5 wt% CP relative to the total weight of RCA having said given size fraction.

[0124] Preferably, the recycled concrete aggregate RCA obtained in a given size fraction of 1 mm or more comprises 5 to 20 wt. % of NA having a particle size smaller than the given size fraction, and preferably comprises 7 to 15 wt. % of NA having a particle size smaller than the given size fraction, relative to the total weight of RCA having the given size fraction.

[0125] In particular, the recycled concrete aggregate RCA obtained with a given size fraction of 1 mm or more comprises 5 to 35 wt. %, preferably 10 to 30 wt. %, even more preferably 15 to 25 wt. % of residual mortar relative to the total weight of the RCA having said given size fraction.

[0126] As defined above, the content of CP, the content of NA having the given particle size, the content of NA having a particle size smaller than the given particle size, and the content of residual mortar of RCA obtained with a given particle size of 1 mm or greater are obtained by selectively dissolving CP in the RCA with hydrochloric acid, weighing and measuring the above-mentioned various components.

[0127] At the end of step ii), in particular at the end of step ii-1) and step ii-2), the recycle fines are separated or recovered. They preferably comprise at least 75% by weight of the CP contained in the initial concrete to be recycled, whereas the prior art comminution step, optionally followed by a screening step, results in recycle fines containing less than 25% by weight of the CP contained in the initial concrete to be recycled.

[0128] Preferably, the recycle fines also contain NA having a particle size of less than 1 mm.

[0129] In the recycled fines, NA with a particle size less than 1 mm and cement slurry may be separated, combined or partially combined, usually partially combined.

[0130] Steps i) and ii) of the method are so effective that very little cement paste adheres to the NA in the RCA. This makes it possible to optimize the subsequent carbonation step iii), in particular by promoting the entry and diffusion of carbon dioxide into the pore volume of the cement paste containing the adherent residual cementitious matrix of the carbonizable reactive phases, in particular portlandite, lime and calcium silicate hydrate (CSH).

[0131] Likewise, steps i) and ii) of the method are so effective that the vast majority of the cement paste is present in the recycled fines in a very fine particle size and is riddled with microcracks. In particular, the recycled fines are in the form of very fine particles (at least 45% by weight, with a particle size < 0.25 mm, relative to the total weight of recycled fines recovered) and are fully available for carbonation. This makes it possible to optimize the subsequent carbonation step iv), in particular by promoting the entry and diffusion of carbon dioxide into the pore volume of the cement paste containing carbonizable reactive phases, in particular portlandite, lime and calcium silicate hydrate (CSH).

[0132] Finally, by the combination of step i) and step ii), a recycled aggregate is obtained comprising only bare natural aggregate and natural aggregate combined with adhering residual cementitious matrix, while a comminution step optionally followed by one or more screening steps results in a recycled aggregate with a high content of cementitious matrix, with some recycled aggregate consisting only of cementitious matrix (residual mortar) with little or no natural aggregate NA, which is not conducive to the subsequent carbonization step.

[0133] The method of the present invention is effective because it makes it possible to obtain RCA of each given particle size of 1 mm or more with high cleanliness.

[0134] In the RCA of the present invention, mortar (with a particle size smaller than CP+NA of the given particle size) is unevenly distributed / adhered around NA having the given particle size. In practice, this results in obtaining most clean RCA (i.e. bare natural aggregate or clean natural aggregate) and a few unclean RCA (i.e. natural aggregate or unclean aggregate combined with adhered mortar).

[0135] In particular, at the end of step ii), in particular at the end of step ii-1) and step ii-2), the recycled concrete aggregate RCA obtained with a given particle size of 1 mm or greater than 1 mm preferably contains at least 50% by weight of clean natural aggregate with the given particle size (i.e. bare natural aggregate or clean RCA with the given particle size), more preferably 55% to 85% by weight of clean natural aggregate with the given particle size (i.e. bare natural aggregate or clean RCA with the given particle size), even more preferably 60% to 75% by weight of clean natural aggregate with the given particle size (i.e. bare natural aggregate or clean RCA with the given particle size), relative to the total weight of RCA with the given particle size.

[0136] Therefore, at the end of step ii), in particular at the end of step ii-1) and step ii-2), the recycled concrete aggregate RCA obtained with a given particle size of 1 mm or greater than 1 mm preferably contains less than 50% by weight of unclean natural aggregate with the given particle size (i.e. natural aggregate with the given particle size combined with adhering residual mortar or unclean RCA), more preferably 15% to 45% by weight of unclean natural aggregate with the given particle size (i.e. natural aggregate with the given particle size combined with adhering residual mortar or unclean RCA), even more preferably 25% to 40% by weight of unclean natural aggregate with the given particle size (i.e. natural aggregate with the given particle size combined with adhering residual mortar or unclean RCA).

[0137] Clean RCA and unclean RCA as defined above, wherein the content of RCA obtained at a given particle size of 1 mm or greater than 1 mm is obtained by the following steps: separating the clean RCA and unclean RCA by optical and / or visual sorting, and then confirming the proportion of CP in the clean RCA and unclean RCA by selectively dissolving the CP in the clean RCA and unclean RCA with hydrochloric acid, weighing and measuring them.

[0138] The method of the present invention may comprise multiple microwave treatment steps i), multiple grinding steps ii-1) and multiple screening steps ii-2), and preferably comprises multiple consecutive microwave treatment steps, grinding steps ii-1) and screening steps ii-2).

[0139] Step a)

[0140] The method may further comprise at least one step a) of cleaning the recycled aggregate RCA. This reduces the proportion of cementitious matrix (residual mortar) in the recycled aggregate RCA, helps to improve the cleanliness of the recycled aggregate RCA, and increases the recovery ratio of recycled fines.

[0141] Step a) is preferably carried out by grinding, in particular using a rotary screen or a gyratory screen.

[0142] Abrasion is a well-known mechanical method for surface cleaning.

[0143] Step a) is preferably carried out after the grinding step ii-1).

[0144] Step a) may be performed simultaneously with the screening step ii-2) (ie, accompanying the screening step ii-2), before or after the screening step ii-2), and preferably simultaneously with the screening step ii-2)).

[0145] If step a) and step ii-2) are carried out simultaneously, they can be carried out using a rotary screen or a gyratory screen.

[0146] If step a) and step ii-2) are not carried out simultaneously, the grinding step a) can be carried out in a rotating drum with or without an elevator.

[0147] If a plurality of screening steps (eg step ii-2a) and step ii-2b)) are performed, the method may comprise a plurality of cleaning steps a), in particular a plurality of cleaning steps a) together with, before or after each screening step.

[0148] In order to accelerate step a), in particular to facilitate the grinding of the cementitious matrix (residual mortar), natural aggregate NA may be added to the recycled aggregate RCA before step a).

[0149] The natural aggregate NA may be added at most 99.5 wt%, preferably at most 95 wt%, more preferably at most 50 wt%, relative to the total weight of aggregate (NA+RCA) used in step a).

[0150] Step b)

[0151] The method may also comprise at least one step b) of washing the recycled aggregate RCA. This reduces the proportion of sand and cement paste (fines) residues in the recycled aggregate RCA (ie those adhering to the surface of the RCA).

[0152] Step b) is preferably carried out by washing with water, more preferably by sprinkling or spraying water.

[0153] Step b) can be carried out simultaneously with (i.e. accompanied by) the cleaning or grinding step a), and / or simultaneously with the screening step ii-2), and / or between the cleaning or grinding step a) and the screening step ii-2), and is preferably carried out simultaneously with the screening step ii-2), and optionally simultaneously with the cleaning or grinding step a).

[0154] This also makes it possible to facilitate the entrainment of recycled fines and their separation from the recycled aggregate RCA.

[0155] If multiple screening steps (e.g. step ii-2a) and step ii-2b)) are performed, the method can include multiple washing steps b), in particular together with each screening step ii-2) and / or cleaning step a), or between each cleaning step a) and screening step ii-2).

[0156] According to a preferred embodiment of the present invention, step ii-2) and step a) are carried out simultaneously, in particular when using a rotary screen or a gyratory screen, and in particular preferably in a wet process. The wet process is preferably carried out by sprinkling or spraying water (for example, spraying water, the water evaporated and then condensed in step i) can be reused). In other words, in the wet process, step ii-2), step a) and step b) are carried out simultaneously. This eliminates the recycled fines that may adhere to the surface of the natural aggregate, preventing them from being entrained in the recycled aggregate (RCA), thereby concentrating them in the final part of the recycled fines. Step iv) of the method of the present invention is optional, because only the RCA can be carbonized at the end of step ii) according to step iii) (first variant). The recycled fines obtained at the end of step ii) can then be used directly in cement raw materials, for example for the manufacture of calcium clinker, by adjusting the composition (for example for achieving a specific silicon rate or water hardness rate) by adding other sources of materials used in the raw materials. Compared to using (calcined) natural limestone, the use of recycled fines in cement raw mix helps to conserve natural limestone resources by replacing a portion of the natural limestone used in cement raw mix and does not emit any additional CO2 in the clinkering step, thereby reducing the carbon footprint of the clinker.

[0157] Step iii) of the process of the invention is optional, since according to step iv) (second variant) only the recycled fines are carbonized at the end of step ii). In fact, the RCA produced by steps i) and ii) is so clean that a carbonization step iii) (low CP content of the RCA obtained at a given size fraction of 1 mm or greater) may not be necessary.

[0158] The RCA obtained at the end of step ii) can be used directly for the preparation of new concrete. They contain such a low proportion of residual mortar that their water absorption and grinding properties are 2 to 3 times better than those of the RCA obtained by the methods of the prior art.

[0159] In a third variant of the process, the recycled fines and RCA are carbonized. This allows for the recovery / storage of larger quantities of CO2 and further improves the performance of the RCA.

[0160] Step iii)

[0161] The method may also comprise, in the presence of carbon dioxide, one or more carbonization steps iii) of RCA [corresponding to the fraction F1 recovered at the end of step ii), step ii-1), step ii-2), step ii-2a) or step ii-2b)].

[0162] Step iii) can carbonize the recycled aggregate RCA obtained in the previous step ii) in the presence of carbon dioxide, in particular, can carbonize the recycled aggregate RCA having one or more than one particle size described in the present invention in the presence of carbon dioxide, in particular, having a particle size from G m To G M , G m To G1 and / or G m Recycled aggregate RCA of one or more than one particle size to G2.

[0163] In step iii), the CP adhered to the surface of the RCA is carbonized.

[0164] At the end of step ii), in particular at the end of step ii-1) and step ii-2), the RCA comprises NA bound to small amounts of CP distributed in the micropores generated by step i). This makes it possible to optimize the carbonation step iii), in particular by promoting the entry and diffusion of carbon dioxide into the cement paste containing carbonizable reactive phases, in particular portlandite, lime and calcium silicate hydrate (CSH).

[0165] Step iii) is preferably carried out in the presence of a CO2-containing gas, preferably comprising at least 1 mol% CO2, more preferably at least 10 mol% CO2, and most preferably at least 15 mol% CO2, relative to the total moles of the gas.

[0166] Step iii) is preferably carried out in the presence of a gas containing CO 2 , preferably comprising at least 5% by volume of CO 2 , more preferably at least 10% by volume of CO 2 , relative to the total volume of the gas.

[0167] The carbon dioxide may come from fumes containing CO2, such as CO2-rich biogas streams from methanogens or biomass power plants, or from fumes from industrial emitters such as cement plants or thermal power plants, or be prepared from a source of CO2 which may or may not have been previously stored.

[0168] The CO2-containing smoke preferably contains at least 15 mol% CO2 relative to the total moles of gases found in the smoke, or at least 15 volume% CO2 relative to the total volume of gases found in the smoke.

[0169] The CO2-containing fumes may also contain other elements, in particular molecular nitrogen N2, molecular oxygen O2 and optionally water.

[0170] The biogas stream may contain from about 70 mol % to about 90 mol % CO 2 relative to the total moles of biogas, or from about 70 vol % to about 90 vol % CO 2 relative to the total volume of biogas.

[0171] In step iii), the recycled aggregates RCA may be introduced into a rotating drum or other reactor where they may be contacted with a gas containing carbon dioxide.

[0172] Step iii) can be carried out at a CO2 partial pressure of about 0.1 bar to about 100 bar, preferably about 0.1 bar to about 5 bar (ie, 250 to 12,000 times the CO2 partial pressure of about 415 ppm in the Earth's atmosphere).

[0173] Step iii) may be performed at a temperature of about 18°C ​​to about 100°C, preferably at a temperature of about 20°C to about 80°C.

[0174] Step iii) may be performed at a relative humidity of about 0% to about 100%, preferably about 10% to about 90%, even more preferably about 40% to about 70%.

[0175] At the end of step iii), the carbonized recycled aggregate or CRCA complies with the NF EN 12620 standard, in particular with respect to water absorption and / or resistance to crumbling, and / or density after oven drying, and / or resistance to abrasion, and preferably at least with respect to water absorption and resistance to abrasion.

[0176] By carbonizing the recycled aggregate RCA, a homogeneous and higher quality carbonized recycled aggregate CRCA is obtained, which can be used to prepare new concrete, especially for making new structures. Step ii-2) and step iii) can be performed simultaneously.

[0177] Carbonization is directed to the reactive phase, ie the cement paste CP adhering to the residual cementitious matrix. At the end of step iii), a carbonized recycled aggregate or CRCA is obtained, comprising bare natural aggregate and natural aggregate combined with a residual cementitious matrix, wherein the cement paste is carbonized, preferably adhering to the natural aggregate NA.

[0178] Step iv)

[0179] The process may also comprise one or more steps iv) of carbonizing the recycled fines in the presence of carbon dioxide [corresponding to the fraction F2 recovered at the end of step ii), step ii-1), step ii-2), step ii-2a) or step ii-2b)].

[0180] Carbonization is directed to the reactive phase, ie the CP in the recycle fines. At the end of step iv), what is obtained is carbonized recycle fines comprising a mixture of NA smaller than 1 mm and carbonized CP.

[0181] The carbonation of recycled fines allows the storage of carbon dioxide and the obtaining of carbonated fines that may be pozzolanic and / or hydraulically active. They can then be used as a mineral additive in concrete to replace cement (e.g. CEM I or CEMII), or as a cement component to make blended cements. For example, the use of carbonated fines as a mineral additive to replace Portland cement in the formulation of structural concrete (buildings) or non-structural concrete (concrete blocks, masonry units, slabs, capping stones, technical mortars) reduces the carbon footprint of concrete. This reduction results from the lower proportion of Portland cement in the concrete and the amount of carbon captured in the carbonate fines, which then act as a carbon sink.

[0182] In other words, the carbonized recycled fines obtained according to the above method can be used as a means of storing CO2 and / or as a replacement for all or part of cement. The use of carbonized fines as an active mineral additive in concrete formulations reduces the carbon footprint of concrete, which is proportional to the rate at which the carbonized fines replace cement.

[0183] When recycled fines from step ii) are used as mineral additive, they are preferably ground prior to carbonization step iv), for example until a particle size of less than about 80 μm, preferably about 5 μm to about 20 μm, is obtained.

[0184] Step iv) is preferably carried out in the presence of a gas containing CO2, preferably containing at least 1 mol% CO2, more preferably at least 5 mol% CO2, and most preferably at least 10 mol% CO2, relative to the total moles of the gas.

[0185] Step iv) is preferably carried out in the presence of a gas containing CO 2 , preferably comprising at least 5% by volume of CO 2 , and more preferably at least 10% by volume of CO 2 , relative to the total volume of the gas.

[0186] The carbon dioxide may come from fumes containing CO2, such as CO2-rich biogas streams from methanogens or biomass power plants, or fumes from industrial emitters such as cement plants or thermal power plants, or may be prepared from a source of CO2 which may or may not have been previously stored.

[0187] The CO2-containing smoke preferably contains at least 10 mol% CO2 relative to the total number of moles of gases in the smoke, or at least 10 volume% CO2 relative to the total volume of gases in the smoke.

[0188] The CO2-containing fumes may also contain other elements, in particular molecular nitrogen N2, molecular oxygen O2 and optionally water.

[0189] The biogas stream may contain from about 70% to about 90% CO2 by volume relative to the total volume of biogas, or from about 70% to about 90% CO2 by mole relative to the total number of moles of biogas.

[0190] In step iv), the recycled fines may be introduced into a rotating drum or other arbitrary reactor where they may be contacted with a gas containing carbon dioxide.

[0191] Step iv) can be carried out at a CO 2 partial pressure of about 0.1 bar to about 100 bar, preferably about 0.1 bar to about 5 bar (ie, 240 to 12,000 times the CO 2 partial pressure in the atmosphere -0.415 mbar).

[0192] Step iv) may be performed at a temperature of about 18°C ​​to about 100°C, preferably at a temperature of about 20°C to about 80°C.

[0193] Step iv) may be performed at a relative humidity of 0% to about 100%, preferably at a relative humidity of about 10% to about 90%.

[0194] Accelerated carbonization of the fines produces carbonized recycle fines that can store up to 15 wt% CO2, ie, up to about 150 kg of CO2 per ton of fines.

[0195] Step 10)

[0196] The method may also include in step i ) The previous step i0) of crushing the construction and / or demolition concrete to form concrete blocks from the construction and / or demolition, the size of which is in the order of centimeters, such as in step i ) Dimensions implemented in .

[0197] The comminution step i0) can be carried out using a crusher, such as a gravel crusher or a jaw crusher, a cone crusher, a gyratory crusher, an impact crusher, a hammer crusher or a centrifugal rotor crusher.

[0198] According to a preferred embodiment of the present invention, step i) is carried out directly after step i0) (without an intermediate step).

[0199] According to a preferred embodiment of the present invention, the process does not comprise any step i0) and one or more steps between step i) involving a liquid phase.

[0200] The method of the invention makes it possible to obtain, from concrete blocks for construction and / or demolition objects, a distribution between aggregates and fines which is close to the initial distribution of the base concrete, i.e. about 70% to 90% by weight of recycled aggregates RCA or carbonated recycled aggregates CRCA (fraction F1, carbonated or non-carbonated), and 10% to 30% by weight of fines (fraction F2, carbonated or non-carbonated), relative to the total weight of the concrete blocks for construction and / or demolition objects, it being understood that at least one of the fractions F1 or F2 is carbonated.

[0201] In particular, the combined use of microwave treatment, mechanical treatment and carbonization of fines and / or RCA in the presence of carbon dioxide can recycle concrete waste from construction and / or demolition.

[0202] The second subject of the present invention is a recycling device, which implements the recycling method according to the first subject of the present invention, characterized in that the recycling device comprises:

[0203] - at least one microwave tunnel for forming micro-cracked concrete blocks from centimetre-sized concrete blocks produced from construction and / or demolition works,

[0204] - at least one roller crusher for crushing micro-cracked concrete blocks and releasing recycled aggregate (RCA), said recycled aggregate comprising bare natural aggregate and natural aggregate combined with an adhering residual cementitious matrix; and recycled fines,

[0205] - at least one vibrating screen, gyratory screen or rotary screen for separating recycled aggregate from recycled fines, optionally cleaning it and optionally washing it, and

[0206] - At least one carbonization reactor for forming carbonized recycled aggregate (CRCA) and / or carbonized recycled fines.

[0207] A rotary screen or gyratory screen is preferably used to separate the recycled aggregate from the recycled fines and to clean and wash them.

[0208] The various elements used in the system are as defined in the first subject matter of the invention.

[0209] A third subject of the invention is a method for recycling concrete from construction and / or demolition objects, characterized in that it comprises the following steps:

[0210] i) one or more steps of microwave treatment of centimeter-sized concrete blocks from construction and / or demolition to form micro-cracked concrete blocks, and

[0211] ii) one or more mechanical treatment steps to enable extraction of recycled aggregate (RCA) from said micro-cracked concrete blocks, which comprises bare natural aggregate and natural aggregate combined with adhering residual cementitious matrix (or residual mortar); and recycled fines,

[0212] The process lacks step iii) and step iv) (i.e. the step of carbonizing the RCA obtained in step ii) and recycling fines) as defined in the present invention.

[0213] As explained above in the first subject of the present invention, the combination of step i) and step ii), in particular step i), step ii-1) and step ii-2), makes it possible to obtain recycled aggregate RCA, the structure of which is as close as possible to the natural aggregate NA of the initial demolition and / or building concrete, and therefore has a high degree of cleanliness.

[0214] Therefore, steps i) and ii) of the inventive method according to the third subject of the present invention produce RCA aggregates with high cleanliness and a large amount of fine powder, because most of the RCA has removed the residual mortar (and cement paste contained in the mortar) adhering to the NA.

[0215] Steps i) and ii) of the method according to the third subject of the present invention are so effective that very little cement slurry adheres to the NA in the RCA. Similarly, steps i) and ii) of the method according to the third subject of the present invention are so effective that the vast majority of cement slurry is present in the recycled fines in a very fine particle size.

[0216] Step ii) preferably comprises at least one step ii-1) of grinding the microcracked concrete block. The method may comprise a plurality of grinding steps ii-1).

[0217] Step ii) may further comprise at least one screening step ii-2), in particular after step ii-1. Step ii) may comprise one or more than one screening step ii-2).

[0218] The method of the present invention, in particular step ii), may comprise a plurality of grinding steps ii-1) and a plurality of screening steps ii-2).

[0219] The method may further comprise at least one step a) of cleaning the RCA.

[0220] The method may further comprise at least one step b) of washing the RCA.

[0221] The method may also comprise, before step i), a step i0) of crushing concrete of the construction and / or demolition object in centimeter sizes to form concrete blocks from the construction and / or demolition object in the sizes implemented in step i).

[0222] Steps i), step ii), step ii-1), step ii-2), step a), step b) and step i0) of the method according to the third subject of the present invention are as defined in the first subject of the present invention.

[0223] The method according to the third subject of the invention therefore makes it possible to isolate the RCA obtained directly in step ii). In other words, it corresponds to a method for manufacturing RCA.

[0224] According to the third subject, the recycled fines obtained at the end of step ii) of the method can be used directly in the cement raw meal, for example for the manufacture of calcium clinker, by adjusting the composition (for example to achieve a specific silica content or hydraulic content) by adding other sources of materials used in the raw materials. Compared to the use of (calcined) natural limestone, the use of recycled fines in the cement raw meal helps to preserve natural limestone resources by replacing a part of the natural limestone used in the cement raw meal, and does not emit any additional carbon dioxide in the clinkering step, thereby reducing the carbon footprint of the clinker.

[0225] The RCA obtained at the end of step ii) of the method according to the third subject matter can be used directly for the preparation of new concrete.

[0226] The fourth subject of the present invention is a recycled aggregate (RCA) obtained by the method according to the first subject of the present invention or the method according to the third subject of the present invention, characterized in that the RCA having a given particle size of 1 mm or greater contains at least 50% by weight of clean natural aggregate having the given particle size (i.e. bare natural aggregate or clean RCA having the given particle size), more preferably 55% to 85% by weight of clean natural aggregate having the given particle size (i.e. bare natural aggregate or clean RCA having the given particle size), and even more preferably 60% to 75% by weight of clean natural aggregate having the given particle size (i.e. bare natural aggregate or clean RCA having the given particle size), relative to the total weight of the RCA having the given particle size.

[0227] Therefore, the recycled concrete aggregate RCA having a given particle size of 1 mm or more preferably contains less than 50 wt.% of unclean natural aggregate having the given particle size (i.e., natural aggregate or unclean RCA combined with adhering residual mortar having the given particle size), more preferably 15 wt.% to 45 wt.% of unclean natural aggregate having the given particle size (i.e., natural aggregate or unclean RCA associated with adhering residual mortar having the given particle size), and even more preferably 25 wt.% to 40 wt.% of unclean natural aggregate having the given particle size (i.e., natural aggregate or unclean RCA combined with adhering residual mortar having the given particle size), relative to the total weight of the RCA having the given particle size.

[0228] In particular, RCA having a given size fraction of 1 mm or more comprises at most 10 wt% CP, preferably at most 8 wt% CP, even more preferably at most 5 wt% CP, relative to the total weight of RCA having said given size fraction.

[0229] The recycled concrete aggregate RCA having a given particle size of 1 mm or more preferably contains 65 wt.% to 95 wt.% of NA having the given particle size, more preferably 70 wt.% to 90 wt.% of NA having the given particle size, and even more preferably 75 wt.% to 85 wt.% of NA having the given particle size, relative to the total weight of RCA having the given particle size.

[0230] Preferably, the recycled concrete aggregate RCA having a given particle size of 1 mm or more comprises 5 to 20 wt % of NA having a particle size smaller than the given particle size, and preferably comprises 7 to 15 wt % of NA having a particle size smaller than the given particle size, relative to the total weight of the RCA having the given particle size.

[0231] In particular, recycled concrete aggregate RCA having a given particle size of 1 mm or more comprises 5 to 35 wt. %, preferably 10 to 30 wt. %, even more preferably 15 to 25 wt. % of residual mortar relative to the total weight of RCA having said given particle size. BRIEF DESCRIPTION OF THE DRAWINGS

[0232] The present invention is illustrated in the accompanying drawings:

[0233] Figure 1 The fracturing of concrete according to the method of the background art is shown, and the fracturing of concrete according to the method of the present invention is compared.

[0234] Figure 2 A schematic diagram showing the various steps of the method of the present invention is shown.

[0235] Figure 3 It is shown that the RCA cleanliness is determined by the variation of the residual CP (in wt. %) according to the size of the RCA according to the method of the present invention and in comparison with the reference method; and the RCA water absorption (in %) is determined according to the size of the RCA.

[0236] FIG. 4 shows the morphological analysis of the components of the initial concrete and the RCA at the end of the method according to the invention, compared with the morphological analysis of the reference method.

[0237] Figure 5 The performance of the method according to the invention is shown relative to a reference method and relative to the theoretical limit.

[0238] Figure 6 The performance of the method according to the invention is shown relative to a reference method and relative to the theoretical limit.

[0239] Other characteristics and advantages of the invention will become apparent from the description of a non-limiting example of a method according to the invention. Example

[0240] Example 1: Description of the method according to the invention and the method of the background art not according to the invention

[0241] Figure 1 Concrete fracturing diagram including a method according to the background art ( Figure 1 a)) and concrete fracturing diagram using the method of the present invention ( Figure 1 b)).

[0242] exist Figure 1 In a), the fracturing between NA and mortar is random and non-selective. It produces RCA with a low NA content (<60 wt. % NA relative to the total weight of RCA) and a high CP content (>10 wt. % CP relative to the total weight of RCA), which has a high potential for transgranular fracture of the original natural aggregate NA. As a result, an aggregate made entirely of a cementitious matrix can be formed, while the natural aggregate NA retaining the original structure is released only to a limited extent. After fracturing, a recycled concrete aggregate (RCA) is mainly obtained: a hybrid aggregate composed of natural aggregate fragments and a high proportion of cementitious matrix or mortar in the hybrid aggregate. Therefore, the recycled fines produced by fracturing are small, and the concentration of these fines does not exceed 25% of the CP in the initial concrete to be recycled.

[0243] exist Figure 1b), according to the method of the present invention, the fracturing of the concrete is selective between NA and mortar, thereby avoiding the fragmentation of the original natural aggregate NA and facilitating the release of the natural aggregate NA and the bonding matrix with the original structure preserved. The cement paste in the micro-cracked bonding matrix will produce fine powder, which may be carbonized or not, and whose particle size is easily separated from the particle size of the aggregate. On the surface of the released natural aggregate, there may be a small amount of adhered residual bonding matrix, which may be carbonized or not to obtain recycled aggregate RCA or carbonized recycled aggregate CRCA with performance as good as that of the original natural aggregate. In other words, the fracturing of the concrete according to the method of the present invention is conducive to the aggregation of NA with a low content of adhered mortar in RCA without changing the particle size and mechanical properties of NA, and is conducive to the recovery of fine powder particle size CP contained in the initial concrete to be recycled. Micro-fracture of CP gathers most of the CP in the form of fines in the initial concrete to be recycled and promotes carbonization of CP in the fines and / or carbonization of a small amount of CP adhering to the surface of RCA. Carbonization of RCA produces CRCA with performance levels as good as NA.

[0244] Figure 2 The invention shows a step i) of microwave treatment of concrete blocks of construction and / or demolition in a microwave tunnel to form micro-cracked concrete blocks. These blocks are then ground in a roller crusher in step ii-1) to form a mixture of recycled aggregate RCA with different particle sizes; and recycled fine powder. For example, grinding ii-1) can obtain a particle size of 8 mm or less. A first screening or sieving step ii-2a) is then carried out using a rotary screen to extract a particle size of G 1' Recycled aggregate with a particle size of less than G1 (e.g., a particle size of 4 mm to 8 mm); and a mixture of recycled fines and recycled aggregate with a particle size of less than G1 (particle size less than 4 mm).

[0245] Subsequently, the particle size G 1' The clean recycled aggregate RCA to G1 is carbonized in a carbonization reactor by step iii) to form a first CRCA particle size. Using a rotary screen, the recycled fines and recycled aggregate with a particle size < G1 are further screened or sieved in step ii-2b) to extract the particle size of G 2' - Recycled aggregates RCA of G2 (e.g. particle size or fraction of 1 mm to 4 mm); and recycled fines (particle size less than 1 mm).

[0246] Subsequently, the particle size G 2' The clean recycled aggregate to G2 is carbonized in the carbonization reactor through step iii) to form a second CRCA fraction and / or recycled fines which is carbonized in the carbonization reactor in step iv).

[0247] Optionally, the concrete blocks used in step i) have a size in the centimeter range (e.g. ≤ 30 mm) and can be obtained by crushing construction and / or demolition concrete, preferably using a gravel crusher or a jaw crusher [step i0)].

[0248] In step ii-2a) and step ii-2b), the steps of grinding a) and washing b) (spraying water) are preferably performed simultaneously with the respective steps in step ii-2a) and step ii-2b).

[0249] Example 2: Recycling of concrete from construction and / or demolition using the method according to the invention

[0250] 2.1 Production and properties of concrete samples

[0251] The concrete was prepared from cement and crushed siliceous natural aggregate (NA) with a particle size of less than 8 mm and a water / cement ratio of 0.6.

[0252] 2.1.1 The cement used is Lafarge CEM I from Le Teil plant. Its strength grade is 52.5R, i.e. fast setting. It complies with the requirements of European standard EN 197-1.

[0253] The physical and mechanical properties of the cement used are as follows:

[0254] - Blaine surface area = 4160cm 2 / g, and

[0255] - Density = 3.15 g / cm 3 .

[0256] 2.1.2 The natural aggregate (NA) used is a mixture of sand (S) and gravel (G) from the Palvadeau sandpit (Saint-Christophe-du-Ligneron) of crushed siliceous type. The characteristics of this aggregate are as follows:

[0257] - Density = 2640kg / m 3 ,

[0258] - Absorption coefficient = 0.7%,

[0259] - Chloride < 0.001%,

[0260] - water-soluble sulfate < 0.01%, and

[0261] - Active alkali content = 0.0022%.

[0262] Table 1 below describes the particle size distribution of NA used to prepare concrete, more specifically the weight % (mass fraction) of five different particle sizes relative to the total weight of natural aggregate NA used to prepare concrete, the five different particle sizes being 4 / 8 mm, 2 / 4 mm, 1 / 2 mm, 0.25 / 1 mm and 0 / 0.25 mm.

[0263]

[0264] Table 1

[0265] These mass fractions are interpreted as average values ​​of the actual NA components of the concrete used below. The last row of Table 1 defines the NA fraction 0 / 1 mm as described below. This fraction combines the NA fractions 0.25 / 1 mm and 0 / 0.25 mm.

[0266] 2.1.3 Concrete formula

[0267] The ratios of binders (cement and high-efficiency water reducing agent), water and NA used to produce concrete are shown in Table 2 below:

[0268]

[0269] Table 2

[0270] A number of concrete samples were prepared by mixing the components in a mortar mixer at low speed (62 rpm) for 60 seconds, high speed (125 rpm) for 40 seconds, pausing for 90 seconds, and then high speed (125 rpm) for 60 seconds; the mixture was then poured into a gray polypropylene cylindrical mold with a diameter of 25 mm and a height of 30 mm. The mold was vibrated on a vibration table for 2×10 seconds. This resulted in the formation of a number of concrete cylinders with controlled composition and shape, the largest dimension of which was about 30 mm.

[0271] The concrete cylinders were then stored under cellophane in a room conditioned to 19°C for 28 days to allow the concrete to cure.

[0272] After 28 days of curing in a greenhouse, the cylindrical concrete samples were oven dried at 80 °C for 48 hours. This time was determined after testing a batch of aggregate that was weighed regularly until a constant mass (Δm < 0.1%) was reached. This drying method ensures the reproducibility of the produced concrete samples by giving them a controlled moisture content comparable to naturally aged concrete.

[0273] After curing and storage, the composition of the concrete in the samples was determined by dissolving the CP in 19 wt% hydrochloric acid. The values ​​in Table 3 below show the range of composition values ​​measured on a number of 30 mm concrete samples, each of which was dissolved individually. This made it possible to assess the variability of the composition of the concrete samples used.

[0274]

[0275] Table 3

[0276] 2.2 Implementation of the method of the present invention

[0277] 2.2.1 Microwave fracturing step i)

[0278] The microwave workbench used is a single-mode cavity waveguide manufactured by SAIREM, which has the following features:

[0279] - Frequency = 2450 ± 25 MHz,

[0280] - Output power = 2000 ± < 0.1% watts,

[0281] - Maximum operating power = 1700 watts,

[0282] - Waveguide = WR340 (rectangular cross section 86 x 43 mm),

[0283] - Ripple < 0.3%RMS, and

[0284] - Magnetron cooling system: water.

[0285] The microwave bench can treat one 30 mm concrete sample at a time at a given power and for a given time. The cylindrical concrete sample is placed in a quartz tube, which serves as a sample holder, and the tube is placed in the chimney of the microwave bench. Each sample is treated for 4 minutes at an incident microwave power of 1.5 kW. The temperature reached on the concrete surface is 450°C to over 600°C (the limit can be measured by the infrared thermometer used).

[0286] 2.2.2 Machining step ii)

[0287] 2.2.2.1 Non-impact crushing (step i-1)

[0288] After microwave treatment, non-impact crushing was performed using a manual hydraulic press (Specac Atlas 15T). The concrete samples were compressed individually. The stroke of the hydraulic press stopped at 8 mm from the surface where the RCA was placed, corresponding to the maximum dimension of the concrete sample NA.

[0289] 2.2.2.2 Screening (step ii-2)

[0290] The pulverized sample was then dry screened on standard 8 mm, 4 mm, 2 mm, 1 mm and 0.25 mm square mesh sieves to produce 4 / 8 mm, 2 / 4 mm, 1 / 2 mm, 0.250 / 1 mm and 0 / 0.25 mm fractions.

[0291] 2.2.2.3 Grinding (step a)

[0292] Recycled concrete aggregate (RCA) of 1 / 4 mm and 4 / 8 mm size fractions produced by crushing followed by screening were ground for a short time in a cylindrical metal can with an inner diameter of 10 cm and a rotation speed of 100 rpm. The grinding charge consisted of 336 g of 20 mm alumina beads and 200 ml of water. The product was then rescreened at 8 mm and 4 mm to separate 8 mm and 4 mm RCA from the abrasive fines, respectively.

[0293] At the end of step ii-1), step ii-2) and step a), fine powders of various size fractions are recycled and collected.

[0294] 2.2.3 Carbonization of fine powder (step iii))

[0295] The obtained fine powder was ground to 80 μm using an automatic mortar and pestle, with an average particle size of d 50 = about 10μm. This fineness is reasonable for using carbonized fine powder as a mineral additive. The step of carbonizing the ground fine powder is carried out in the form of a suspension in a stirred reactor with an effective volume of 300ml. The suspension used consists of a mixture of 15 grams of recycled concrete fine powder and 150 ml of distilled water. Its mixing is ensured by a mobile stirrer rotating at 800rpm. The carbonization reactor is operated at a CO2 partial pressure of 5 bar and a controlled temperature of 60°C. The carbonization test lasts 20 hours, during which the consumption of CO2 by the fine powder is continuously measured. The final carbonization rate of the carbonate fine powder is obtained by thermogravimetric analysis (TGA) or by total carbon measurement (CHNS analysis).

[0296] Comparative Example 3: Recycling of concrete from construction and / or demolition using a method not according to the invention

[0297] The method of the invention was compared with a non-impact crushing method, which represents the most effective technology for the production of recycled concrete aggregates. This comparative method, hereinafter referred to as the "reference method", was carried out using the same concrete samples as described in point 2.1. The reference method consisted of mechanical treatment with non-impact crushing and screening steps under the same conditions as described in point 2.2.

[0298] The fine powder was subjected to a carbonization step as described in Example 2, section 2.2.3.

[0299] Example 4: Performance of the method of the present invention

[0300] 4.1 Performance evaluation criteria

[0301] The performance criteria used to characterize the performance of the method relate to the quality and use characteristics of recycled concrete aggregate (RCA) and recycled concrete fines.

[0302] For recycled concrete aggregate (RCA):

[0303] • quality:

[0304] - CP content of a given RCA fraction (in wt%),

[0305] - the clean RCA content of a given RCA fraction (i.e. RCA with CP content < 5 wt. %), and

[0306] - Content of natural aggregate (NA) of the same size as RCA (wt%).

[0307] • Usage characteristics:

[0308] - Water absorption of RCA determined by the WA24 method. This test measures the water content of RCA after drying according to the NF EN 1097-5 standard. It is expressed as a percentage by weight.

[0309] - Wear resistance of the RCA measured by the Micro Deval (MDE) test. This test measures the wear resistance caused by the friction between the RCA and the abrasive load of a steel ball according to standard NF EN 1097-1. The test result is expressed in %, representing the weight percentage of particles smaller than 1.6 mm generated during the test.

[0310] For recycled concrete fines (<1 mm):

[0311] • quality:

[0312] - Content of mortar in the fine powder (<1 mm) produced by this method (wt%)

[0313] - Content of CP (wt%) in the fine powder (<1 mm) produced by this method

[0314] - Fines carbonization rate (weight % of CO2 captured).

[0315] 4.2 Cleanliness of recycled concrete aggregates

[0316] Figure 3The measured values ​​of the cleanliness of RCA according to the variation of the residual CP content (wt%) (left) depending on the particle size of RCA for the method of the present invention (solid circles) and the reference method (open circles) are shown. The content was measured by dissolving RCA with particle sizes of 4 / 8 mm, 2 / 4 mm, 1 / 2 mm, 0.250 / 1 mm and 0 / 0.25 mm in a 19 wt% hydrochloric acid solution.

[0317] There was no overlap between the 95% confidence intervals for the residual CP mass fraction down to an RCA particle size of 0.5 mm, indicating that the RCA produced by the inventive method was significantly cleaner than the RCA produced by the reference method down to an RCA particle size of 0.5 mm.

[0318] Figure 3 Also shown are measured values ​​of water absorption of RCA (expressed in %) (right) as a function of the particle size of RCA for the process of the invention (long dashed line) and the reference process (short dashed line). This value was measured by dissolving RCA of particle sizes 4 / 8 mm, 2 / 4 mm, 1 / 2 mm, 0.250 / 1 mm and 0 / 0.25 mm in 19 wt % hydrochloric acid solution.

[0319] 4.3 Product form in the method of the present invention

[0320] A detailed analysis of the product quality during the process of the invention (compared to the reference process) consists in determining the initial components of the concrete (NA and CP, see Example 2, Section 2.1 for morphology) before and after the process of the invention (compared to the reference process) (Example 2, Section 2.2 and Example 3). The morphology is used to refer to the traceability of the initial components in the product of the process of the invention (compared to the reference process).

[0321] As a reminder, the products used to characterize the performance of the concrete recycling process are 4 / 8RCA, 2 / 4RCA, 1 / 2RCA and fines (particles < 1 mm). The components of interest in the morphological measurements are the natural aggregates 4 / 8NA, 2 / 4NA, 1 / 2NA and fines represented by 0.25 / 1NA, 0 / 0.25NA and CP.

[0322] Figure 4a) and Figure 4b) respectively show in detail this form of the reference method and the method of the present invention. In these figures:

[0323] - Before implementing the method, X i and X' i The initial composition of the concrete samples is described. The composition is the same for both the reference method and the method of the invention.

[0324] - Columns A and A' show the mass distribution of the products (4 / 8RCA, 2 / 4RCA, 1 / 2RCA and fine powder) after implementation according to the reference method and the method according to the invention, respectively. For the reference method (Example 3), the products were separated by screening after crushing, and for the method according to the invention (Example 2, part 2.2), the products were separated by screening after step ii) and step a); their mass fractions were obtained by weighing.

[0325] - Columns B and B' show the morphology of each product (in mass percentage), in other words, the morphology of each fraction in columns A and A': column B1 (or B'1) corresponds to the morphology of 4 / 8 RCA of column A1 (or A'1), column B2 (or B'2) corresponds to the morphology of 2 / 4 RCA of column A2 (or A'2), and so on. The morphology measurement consists of selectively dissolving the CP in each product in 23 wt% hydrochloric acid, followed by screening (and optional grinding), weighing and drying of the dissolved NA fraction. The mass loss after dissolution gives a direct measure of the mass of CP found in the product.

[0326] - Columns C and C' show the observed amounts of clean NA (or bare or clean RCA) and NA combined with adherent residual mortar (or unclean or unclean RCA), as well as the amounts of CP in the selected fractions: Column C1 (or C'1) corresponds to the observation and measurement of the 4 / 8 NA fraction of column B1 (or B'1), Column C2 (or C'2) corresponds to the 2 / 4 NA fraction of column B2 (or B'2), and Column C3 (or C'3) corresponds to the 1 / 2 NA fraction of column B3 (or B'3).

[0327] -X r and X' r denotes the composition of the concrete sample recalculated after the implementation of the reference method and after the implementation of the method according to the invention, respectively. It is established from the values ​​in columns B and B' which give the morphology of the initial composition of the concrete in the product.

[0328] Since the fraction of fines is defined as all particles smaller than 1 mm (0.25 / 1 RCA + 0 / 0.25 RCA), the morphological analysis of the components shows that the method of the invention concentrates 31% of the mass of concrete in this fine fraction (column A' in Figure 4b): 16% in column A'4 + 15% in column A'5), while the reference method only concentrates 12% (column A in Figure 4a): 8% in column A4 + 4% in column A5). Therefore, the method of the invention can concentrate almost three times more fines than the reference method, which can be recycled as cement raw material if they are not carbonated, or as mineral additive if they are carbonated.

[0329] The mass fractions of 4 / 8RCA, 2 / 4RCA and 1 / 2RCA in the method of the present invention are very close to the mass fractions of 4 / 8NA, 2 / 4NA and 1 / 2NA in the initial concrete, which can be explained by the fact that the mass fraction of NA recovered in RCA exceeds 75% or even 80%. In other words, the RCA produced by the method of the present invention contains less than 20 wt% of residual mortar, that is, the CP mass fraction is 5 wt% to 8 wt% (see columns B'1, B'2 and B'3 in Figure 4b).

[0330] In contrast, the NA recycling rate of the RCA of the reference method is 40 wt % to 60 wt %, so the mass fraction of the residual mortar in the RCA is 60 wt % to 40 wt %, that is, the CP mass fraction is 11 % to 21 % (see columns B1, B2, and B3 in Figure 4a).

[0331] For the concrete sample component X r and X' r The recalculation of shows that the method of the present invention better preserves the particle size integrity of the initial NA than the reference method. In fact, the component X' recalculated by the reference method r The 4 / 8NA content in the 100% NA was significantly lower than that obtained by the method of the present invention, which actually resulted in a greater increase in the 2 / 4NA content using the reference method. This is due to the microfracture of the CP caused by the microwave step, thereby avoiding excessive NA fragmentation in the subsequent pulverization step.

[0332] The degree of release (or cleanliness) of NA in RCA was measured by visual sorting, and the CP content of the separated particle sizes (columns C and C') was verified. This measurement demonstrates the selectivity of the method of the present invention in NA recovery, which is provided by the micro-crushing of concrete caused by the microwave treatment step. This selectivity leads to an uneven distribution of residual CP, which is concentrated in a small portion of NA, while the CP content of most RCA is particularly low. These NAs are referred to herein as clean (or bare) NAs. The very high proportion of clean NAs in RCA is a specific feature of the method of the present invention. Release measurements were performed on RCA particle sizes of 4 / 8 mm (columns B1 and B'1), 2 / 4 mm (columns B2 and B'2) and 1 / 2 mm (columns B3 and B'3). On the right side of FIG. 4b, as shown in column C', it can be seen that more than 60% to 70% of the RCA produced by the method of the present invention is clean (i.e., the RCA contains 1.6% to 3.2% CP), and the remaining 30% to 40% of the RCA aggregates CP with a CP content of 3.9% to 10.7%. As shown in column C of FIG. 4a), the release (or cleanliness) of the RCA of the reference method is only 16% to 42%. In summary, for the three RCA particle size categories analyzed, the release (or cleanliness) of the NA of the method of the present invention is twice as high as the release (or cleanliness) of the NA of the reference method.

[0333] The performance and theoretical limits of the method of the present invention are compared with those of the reference method. For example, the theoretical limit of cleanliness of RCA in terms of residual CP content is 0%, while the maximum percentage of 4 / 8 mm NA in 4 / 8 mm RCA is 100%. All percentages are expressed in weight %.

[0334] Figure 5 The performance of the method according to the invention is shown relative to a reference method and relative to the theoretical limit.

[0335] 4.4 Characterization of carbonization

[0336] Aqueous carbonization methods can achieve up to about 80% of the theoretical carbonization limit of a solid, calculated based on its chemical composition.

[0337] The theoretical carbonation limit of fines is directly related to the amount of calcium (Ca) they contain. For each mass unit of fines, this theoretical limit is similar for the fines of the process of the invention and the fines of the reference process, since measurements have shown that they have the same chemical composition. This theoretical limit is between 170 kg and 200 kg CO2 / ton of fines. In contrast, the process of the invention is able to produce 2.6 times more fines than the reference process, so the process of the invention can store up to 2.6 times more CO2 per ton of recycled concrete than the reference process. This represents a CO2 storage potential of 60 kg CO2 / ton of recycled concrete for the process of the invention, compared to 20 kg CO2 / ton of recycled concrete for the reference process, taking into account that the maximum potential for concrete carbonation is estimated on the same basis, i.e. 70 kg CO2 / ton of recycled concrete. Therefore, in fines, the process of the invention can store three times more CO2 than the reference process relative to one ton of recycled concrete (Table 4 below).

[0338]

[0339] Table 4

[0340] The final carbonization rate of the carbonized fine powder is obtained by measuring the total carbon (CHNS analysis).

[0341] Table 5 below lists the results for the fine powders obtained according to the reference method and the method according to the invention.

[0342]

[0343] Table 5

[0344] The experimental measurements confirmed that the carbonization potential of the fine powders of the process according to the invention and the reference process is similar, due to the similarity of their chemical composition. However, these results are very favorable to the fine powders produced by the process according to the invention, which have an increase of +1.3 in carbonization compared to the fine powders produced by the reference process. This result, together with the observation during the fine powder carbonization tests that the fine powders of the carbonization process according to the invention have better kinetics than the fine powders of the reference process, is probably the result of the micro-disintegration of the CP caused by the microwave treatment step, which promotes the transfer of carbon dioxide (CO2) to the elements (calcium) in the CP that can be carbonized.

[0345] Figure 6 The performance of the method according to the invention is shown relative to a reference method and relative to the theoretical limit.

[0346] In all performance criteria measured, the method of the invention was on average 2.3 times more efficient than the reference method.

Claims

1. A method for recycling concrete from construction and / or demolition objects, characterized in that The method comprises at least the following steps: i) one or more steps of microwave treatment of centimeter-sized concrete blocks from construction and / or demolition objects to form microcracked concrete blocks, ii) one or more mechanical processing steps to enable the extraction of recycled aggregate from said micro-cracked concrete blocks, said recycled aggregate comprising bare natural aggregate and natural aggregate combined with an adhering residual cementitious matrix; and recycled fines, And, it is characterized in that the method further comprises: iii) one or more steps of carbonizing the recycled aggregate in the presence of carbon dioxide to form carbonized recycled aggregate, and / or iv) one or more steps of carbonizing the recycle fines in the presence of carbon dioxide to form carbonized recycle fines.

2. The method according to claim 1, characterized in that Concrete blocks from construction and / or demolition have a size of up to 10 cm.

3. The method according to any one of the preceding claims, characterized in that The microwave treatment of step i) is carried out for a period of 30 seconds to 10 minutes.

4. The method according to any one of the preceding claims, characterized in that The microwave treatment i) is carried out at a frequency of 915 MHz to 2450 MHz.

5. The method according to any one of the preceding claims, characterized in that The exposed natural aggregate is selected from gravel, sand and mixtures thereof with a particle size of 1 mm or more; and the natural aggregate combined with the adhesive residual cementitious matrix is ​​selected from gravel, sand and mixtures thereof with a particle size of 1 mm or more.

6. The method according to any one of the preceding claims, characterized in that The adherent residual cementitious matrix combined with the natural aggregate includes natural aggregate having a particle size of less than 1 mm.

7. The method according to any one of the preceding claims, characterized in that Step ii) comprises at least one step ii-1) of grinding the micro-cracked concrete blocks.

8. The method according to claim 7, characterized in that Step ii) further comprises at least one screening step ii-2).

9. The method according to any one of the preceding claims, characterized in that Maximum particle size of recycled aggregate G M At most 45 mm, or at most 25 mm, or at most 11.2 mm, or at most 8 mm, or at most 4 mm.

10. The method according to any one of the preceding claims, characterized in that The recycled aggregate has a particle size of at least 1 mm. m .

11. The method according to any one of the preceding claims, characterized in that The method further comprises at least one step a) of cleaning the recycled aggregate.

12. The method according to any one of the preceding claims, characterized in that The method further comprises at least one step b) of washing the recycled aggregate.

13. The method according to any one of the preceding claims, characterized in that Step iii) is carried out in the presence of a gas comprising at least 10 mol % of CO 2 relative to the total number of moles of the gas.

14. A recycling device for implementing the recycling method defined in any one of the preceding claims, characterized in that The recycling device comprises: - at least one microwave tunnel for forming micro-cracked concrete blocks from centimetre-sized concrete blocks produced from construction and / or demolition works, - at least one roller crusher for crushing micro-cracked concrete blocks and releasing recycled aggregate, said recycled aggregate comprising bare natural aggregate and natural aggregate combined with a cementitious matrix; and recycled fines, - at least one vibrating screen, gyratory screen or rotary screen for separating recycled aggregate from recycled fines, and optionally cleaning and optionally washing them, and - At least one carbonization reactor for forming carbonized recycled aggregate and / or carbonized recycled fines.

15. Recycled aggregate (RCA) obtained according to the method defined in any one of claims 1 to 13, characterized in that The RCA having a given size fraction of 1 mm or more comprises at least 50% by weight of bare natural aggregate having the given size fraction relative to the total weight of the RCA having the given size fraction.

Citation Information

Patent Citations

  • Carbonation of concrete aggregates

    WO2020217232A1